Synthesis and In Vivo Hypolipidemic Effect of Some N-(Benzoylphenyl)-Carboxamide Derivatives in Triton WR-1339-Induced Hyperlipidemic Rats - Kamal Sweidan; Ghassan Abu Sheikha; Ghassan Shattat; Tariq Al-qirim; Majdi Bkhaitan (Universidade de São Paulo, 2022)
Abstract A series of N-(benzoylphenyl)-carboxamide derivatives (2a, 2b, 3a, 3b, 4a, 4b, 5a, 5b, 6a and 6b) was prepared with good yields by reacting the corresponding carbonyl chlorides with aminobenzophenones at room temperature. This was followed by evaluating the hypotriglyceridemic and hypocholesterolemic effects of 3b, 5a and 5b. Triton WR-1339 (300 mg/kg) was intraperitoneally administered to overnight-fasted rats to induce hyperlipidemia. Rats were divided into six groups: control, hyperlipidemic, hyperlipidemic plus compounds 3b, 5a and 5b and hyperlipidemic plus bezafibrate. Results showed that after 18 h of treatment at a dose of 15 mg/kg body weight of each of the test compounds, the elevated plasma levels of triglycerides (TG) and total cholesterol (TC) were significantly lowered by compounds 5b and 3b (p < 0.001) and by 5a (p < 0.0001), compared to the hyperlipidemic control group. Compounds 3b and 5a significantly increased levels of high-density lipoprotein cholesterol (HDL-C) by 58 and 71%, respectively. In addition, compounds 3b and 5a caused significant reduction (p < 0.0001) of low-density lipoprotein cholesterol (LDL-C) levels compared to the control group. These results suggest a promising potential for compounds 3b, 5a and 5b as lipid-lowering agents, which may contribute to reducing the risk of atherosclerosis and cardiovascular disease.